Formulation, nutritional profile, and sensory acceptability of cookies incorporating locally sourced ingredients as complementary foods for toddlers: A strategy for stunting prevention - Yuliana; Rahmi Holinesti; Nabila Tasrif; Ifnalia Rahayu; Afifah Nur Hasanah; Helmizar; Healthy Hidayanti; Yolanda Febriani Naserd; Siti Halipah (Food Chemistry Advances)
This study focuses on the formulation of cookies using local food ingredients as supplementary food for toddlers to prevent stunting, by optimizing nutritional content through a linear program. Stunting is a significant public health problem in many developing countries, including Indonesia, caused by chronic malnutrition in childhood. Cookies are formulated using nutrient-rich ingredients from local sources, such as tilapia fish meal and spinach flour, which are rich in protein, iron, and other essential nutrients. A linear program is used to optimize the nutritional profile of the cookies, ensuring that they meet the specific nutritional needs of toddlers. Nutritional analysis was conducted to evaluate the macronutrient and micronutrient content of the cookies. Sensory evaluation was also conducted to assess the acceptability of the cookies by 7 trained sensory panelists. The results showed that the optimized cookies provided a balanced nutritional profile that addressed the main nutritional deficiencies associated with stunting. The cookies were also found to be highly acceptable in terms of shape, color, aroma, texture, and taste, making them a promising solution to prevent stunting through food products that are easily accessible, nutrient-dense, and tailored to the nutritional needs of toddlers.